Learning curve for endoscopic submucosal dissection of gastric submucosal tumors: is it more difficult than it may seem? - Sun, Chao; Zheng, Zhongqing; Wang, Bangmao (Journal of laparoendoscopic & advanced surgical techniques. Part A, 2014)
Endoscopic submucosal dissection (ESD), as a minimally invasive technique, is gaining wide acceptance for treating epithelial neoplasms. More recently, some pioneers have developed ESD for the treatment of submucosal tumors (SMTs), but characterization of the learning curve is lacking. In this study we aimed to evaluate the learning curve for ESD of gastric SMTs. From September 2008 to April 2011, ESD was performed in 50 consecutive patients with gastric SMTs by a single experienced endoscopist at our high-volume institution. The cumulative sum (CUSUM) method was performed to analyze the shifts in operative time (OT) and consequently to investigate the learning curve. Analysis of the OT using the CUSUM method identified two distinct phases: Phase 1 (the initial 32 cases) and Phase 2 (the remaining 18 cases). Phase 1 represented the initial learning period, whereas Phase 2 showed the more skilled and higher proficiency period, with a significant reduction in OT (90±29 minutes versus 55±20 minutes; P<.0001). The two phases did not differ significantly with respect to patient characteristics and other perioperative parameters. Mastery of operative technique for ESD of SMTs is evident by a decrease in OT identified by CUSUM graphs. For endoscopists competent in basic endoscopic intervention skills, the learning curve should be achieved after approximately 32 cases. Offering this minimally invasive endoscopic intervention does not result in increased complication rate even in the early phase of the learning curve.